Universalisme en partikularisme vandag - Westhiuzen, H. G. van der (Hervormde teologiese studies, 1989)
Universalism and particularism today Today we are heirs to a great variety of conceptions in particularism and universalism. It usually represents a view on world and life that is reflected mutually on domains of church and state. Universalism especially increases in seriousness and extent as is to be noticed in the ecumenical theology and the foundation in the United Nations and the so-called human rights. The proper conception of particularism however, serves a proper conception of universalism.